Intervention in telephone social networks to achieve timely screening of cervical cancer in women in the lambayeque region - Soto-Cáceres , Víctor (2023)
Objectives: To estimate the impact of intervention through telephone social networks in improving Pap smear screening in districts of the Lambayeque region. Material an metodos: Intervention study, two districts (intervention and control) were randomly selected for each province of the Lambayeque region, using Epidat 3.1 231 people were obtained: 115 intervention group and 116 control group; Inclusion criteria: Women aged 30 to 50 living in the six selected districts, who have a cell phone and can read text messages or WhatsApp. Instruments: survey validated by experts applied by two pollsters, messaging sent by specific personnel, supervision by field doctor. It was authorized by the Research Ethics Committee of the UCV and informed consent was applied. Results: The knowledge that both study groups had regarding the Pap test was quite good, however 83% of the total had no knowledge about the IVAA. After 2 months we returned to inquire if they had performed their Pap smear and it was found that in the intervened group on average only 25% had complied; Among the reasons why they had not been carried out, 44% "did not have time", a new reason was that "he was not in his district" 16%. In the control group, only 19% performed it. There is no statistically significant difference between the two groups with respect to post-intervention screening. Conclusions: Despite having sent messages to the cell phone, there was no statistical difference with those who did not receive it for new PAP screenings.